Effects of Diet on the Growth of twospotted Spider Mites - Leonard, Elena; Nechols, James (My University, 2017)
Twospotted spider mites—Tetranychus urticae Koch—are a major pest, and so knowing as much about the pesky creatures as possible will allow those in horticultural fields to prepare better defenses against infestations, and reduce damage if infestation is unavoidable. A few particular points we could take from this experiment are whether any increase in size that may occur leads to a preference, and whether it leads to an increase in population size due to an increase in fecundity of adult female mites. It is commonly understood that the larger a female insect is, generally the more eggs she will lay in her lifetime. As further explained by Alois Honek (1993), the common slope of the fecundity/size relationship is close to 1 and this indicates that female size is a principal constraint on insect potential fecundity. Therefore, knowing whether or not insects will grow larger when feeding on certain food sources will warn us as to how quickly we should expect insect populations to increase. There is currently little to no information about the effects of food on body size in spider mites, and so this experiment could assist in this regard.. If results are positive, we can use the information to assess differences in pest infestation and population growth. If not, then either we can change the test plants or conclude that there is likely no effect of diet whatsoever. However, in this study, we expected to see some difference in the sizes of either population of spider mites due to the contents of their diets. From a previous study done by Teder et. al. (2014) on the correlation between age and size at maturity and diet of over 200 species of insects, it was found that there was in fact a difference in body size for nearly all insect species based on source of diet. Working off of what is already known about correlations between body size and diet, it can be assumed that even in an arachnid population, there will be some significant variation based on diet. Our hypothesis was supported as there was a statistically significant difference (t-test: P=0.02, t=2.36, df=48) in average ody length of the two populations, with the green bean population being the larger of the two (figure 1). The results of this study show that certain plants are more nutritious for twospotted spider mites, which may lead to a preference on their part, giving agricultural and horticultural workers a heads-up as to what plants they should watch more carefully.
Citation: Leonard, E. (2017). Effects of Diet on the Growth of twospotted Spider Mites . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.